Synthesis and cytotoxicity evaluation of sorafenib- and 5-fluorouracil-loaded chitosan, graphene-oxide and folic-acid based nanocarriers for liver and colon cancer - Ruman, Umme (2021)
Nanocarriers-based drug delivery systems have become the new option for treating cancer due to their negligible side effect. Sorafenib (SF) and 5-Fluorouracil (5FU) drugs have severe side effects on the human body. Therefore, new nanocarriers-based drug delivery systems should be implemented to load these drugs. In this study, SF and 5- FU-loaded chitosan nanocarriers with and without graphene oxide (GO) and folic acid (FA) were synthesized to evaluate the anticancer activity on human liver cancer (HepG2) and colon cancer (HT29) cells. All the nanocarriers were prepared by the ionotropic gelation method where drugs were entrapped with chitosan and chitosan/graphene-oxide composite via cross-linking with sodium tripolyphosphate (TPP). The nanocarriers were found uniform size with efficient drug loading and encapsulation. Chitosan nanoparticles (CS NPs) loaded with SF drug (SF-CS-SF NPs) was found 76 nm while folate conjugated SF loaded chitosan NPs (SF-CS-SF-FA NPs) was found 82 nm. Besides, SF and 5-FU loaded CS NPs (SF/5FU-CS-SF NPs) were found 78 nm and FA conjugated SF/5FU loaded CS NPs (SF/5FU-CS-SF-FA NPs) was found 142 nm. Moreover, the GO/CS composite based SF loaded (GO-CS-SF) was found 122 nm and folate conjugated GO/CS composite based SF loaded nanocomposite (GO-CS-SF-FA) was found 164 nm. All the nanoparticles' encapsulation efficiency was found to be 70-80% while nanocomposites encapsulation efficiency was found 80-90%. XRD and FTIR evaluation found the amorphous structure and the chemical bond formation of the nanocarriers, respectively. The in vitro release study showed the sustained release of the drugs from all the nanocarrier systems. The nanocomposites were found slightly slow release compared to nanoparticles. Overall, most of the drug (90%-100%) release was achieved within120 hours for all samples. The cytotoxicity study revealed better anticancer activity compared to the free drugs alone against human hepatocellular carcinoma (HepG2) and human colorectal carcinoma (HT29) cells. The IC50 value for pristine drugs is higher than nanocarriers. Moreover, all the nanocarriers have shown no toxicity to normal fibroblast human dermal fibroblast adult cells (HDFa). This is towards the new generation of drug delivery systems of tailor-made properties with better efficacy and accuracy.